2014
DOI: 10.1021/am5029654
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Nested Inverse Opal Structures as Hierarchically Structured Large-Scale Membranes with Tunable Separation Properties

Abstract: A novel multiscale porous architecture where an individual particle is nested inside a hollow chamber of inverse-opal (IO) frame is created using a large scale self-assembly of core-shell structured colloidal particles and subsequent selective removal of the outer shells of the colloids. Since the nested particle is smaller than the size of individual IO chamber, the interconnected nanochannels are spontaneously formed within the structured frame. The size of internal nanochannels is readily tuned to have high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…They achieved this by selectively etching the SiO 2 shell after backfilling the colloidal ensemble with a photocurable polymer. 446 A method to prepare tubular colloidal crystal arrays was introduced by Li et al by particle infiltration into silicon membranes. 454 Depending on the ratio between the particle and tube diameter, the packing geometries within a single particle strand ranged from hexagonal to cubic and helical arrangement (Figure 23f,g).…”
Section: Colloidal Crystals On Topographically Patternedmentioning
confidence: 99%
“…They achieved this by selectively etching the SiO 2 shell after backfilling the colloidal ensemble with a photocurable polymer. 446 A method to prepare tubular colloidal crystal arrays was introduced by Li et al by particle infiltration into silicon membranes. 454 Depending on the ratio between the particle and tube diameter, the packing geometries within a single particle strand ranged from hexagonal to cubic and helical arrangement (Figure 23f,g).…”
Section: Colloidal Crystals On Topographically Patternedmentioning
confidence: 99%
“…These studies are particularly useful for membrane and sensing applications, and are related to the diffusion through the pores that is necessary for catalytic and electrode applications. CBPM have also been used in other transport applications such as for cell culture, 210,211 for drug delivery, 212,213 and as membranes and filters, 214 applications we do not cover in this review. 86 Reproduced with permission from the American Chemical Society.…”
Section: Wetting Applicationsmentioning
confidence: 99%
“…They demonstrated in their theoretical calculations that DIOs had possibilities as controls over light emission and propagation by shifting the location of silica spheres within the voids. Rhee et al (2014) reported a similar structure of DIO fabricated using UV-curable resin as a backbone material. The DIO containing silica spheres in the polymeric backbone was fabricated for application to a nanoparticle separation system, because the DIO had interconnected nanochannels usable for mesoporous membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for preparation of DIOs have been reported to be applied to optical waveguides and separation systems (Ruhl et al, 2006;Rhee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%